Assessment of yield traits between family groups of the cultured abalone (Haliotis midae) in South Africa - Van Schalkwyk, Hester Josina (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScAgric)--Stellenbosch University, 2012.